Guidelines for the Management of Complications of Diabetes in Saudi Arabia Using Delphi Technique for Consensus Among National Experts - Raed Aldahash; Mohammed A. Batais; Ashraf El-Metwally; Saja Alhosan; Mohammed Alharbi; Mohammed Almutairi; Abdulghani Alsaeed; Mohammed Alsofiani; Mohammed AlMehthel; Mohammed Aldubayee; Khaled Aldossari; Sulieman Alshehri (Clinics and Practice)
(1) Background: Saudi Arabia has one of the leading cases of diabetes globally, with approximately 27.8% of adults suffering from the disease. Given the negative consequences of diabetes mellitus (DM), it is critical to develop guidelines for its management. (2) Methods: After a thorough review of the literature around diabetes management, a diverse panel of 14 clinical experts was identified to participate in the Delphi process. The Delphi process included three rounds to ensure all available evidence was accounted for. (3) Results: The Delphi method concluded with a total of 37 guidelines reviewed and approved by the panelists, followed by verification from a third party in Saudi Arabia. The Delphi and external evaluation confirmed that authentic, relevant, and applicable evidence for diabetes management in Saudi Arabia was accounted for. The process concluded with a list of 37 statements about the management of acute and chronic complications of diabetes in Saudi Arabia. (4) Conclusions: The preparation of contextual evidence for the management of diabetes in Saudi Arabia will be instrumental in addressing the burden of disease in the region. The guidelines offer useful insights into diabetes care, especially by prioritizing early detection and proactive management of complications. They highlight the importance of lifestyle changes and medical therapy. However, due to the ever-changing nature of diabetes, the document must be monitored and updated on a regular basis to ensure its continued relevance and effectiveness.